Outcome of Intermediate Risk Pediatric Febrile Neutropenia – a Single Center Prospective Study from Pakistan - Khan, Muhammad Rahil; Ashraf, Muhammad Shamvil; Iftikhar, Sundus (Infectious Diseases Journal of Pakistan, 2022)
Purpose: Febrile Neutropenia (FN)is an oncological emergency, which requires early recognition and prompt antibiotics administration for better outcome.We aimed to determine the outcome and association of demographic, clinical and laboratory data of intermediate risk pediatric febrile neutropenia treated with piperacillin / tazobactam and amikacin in a tertiary care hospital of Pakistan. Methods: All intermediate risk pediatric febrile neutropenia less than 16 years of ageadmitted in the pediatric oncology ward of The Indus Hospital from May to July 2016 were enrolled prospectively. Relapsed patients, low and high-risk FN were excluded. Outcome defined as success if discharged after completion of antibiotics or as failure if antibiotics changed, antifungal added or need of intensive care due to hemodynamic instability and death. Results: Total 141 episodes occurred in 136 children. Success rate was 83 %(n=117) and failure 17%(n=24). Major reason of failure was change in antibiotics (79.2%) due to persistent fever > 72 hrs.Three deaths occurred in the entire cohort due to probable fungal infection. On multivariable analysis, four independent risk factors were found to be significant for failure- ANC< 100 at presentation (aOR (95% CI):11.45 (1.70-77.19), p= 0.012), CRP=20mg/dl (aOR (95% CI):3.94 (1.03-15.12), p=0.045), respiratory rate (aOR (95% CI):1.48 (1.17-1.88), p=0.001) and heart rate (aOR (95% CI):0.96 (0.93-1.00),p=0.048). Conclusion: Our approach to treat intermediate risk febrile neutropenia was optimal. Strategy of low and high risk needs investigation. Based on our results, scoring model can be formulated for further refinement of our current management. Key Words: Febrile neutropenia, Intermediate risk.